Ataxic form of central pontine myelinolysis - Somarajan A; Paul M; Kabeer K; Krishnapriyam S (Annals of Indian Academy of Neurology, 2007)
Central pontine myelinolysis (CPM), a neurologic disorder caused most frequently by rapid correction of hyponatremia, is characterized by demyelination that affects the central portion of the base of the pons. Central pontine myelinolysis occurs frequently in alcoholism and chronic liver disease. Clinical features usually reflect damage to the descending motor tracts and include spastic tetraparesis, pseudobulbar paralysis and the locked-in syndrome. Cerebellar ataxia with out weakness and pyramidal signs is extremely unusual. There are only very few reports of central pontine myelinolysis presenting as cerebellar ataxia.